The Role of Innovative Technologies in Pedagogical Education - Prof. Bo’riyev H.K. (Zien Journals, 2024)
The rapid evolution of technology presents a transformative opportunity for pedagogical education. This article explores the role of innovative technologies, including AI-powered learning platforms, adaptive learning software, virtual reality (VR) and augmented reality (AR) simulations, and online learning platforms, in shaping the future of learning. We examine the potential benefits of these technologies in personalizing instruction, enhancing engagement, and expanding access to education. However, we also acknowledge the challenges and ethical implications associated with their integration, including the need for responsible implementation, equitable access, and ongoing professional development for educators. The article concludes by emphasizing the importance of striking a balance between technological advancements and human-centered learning to create a more effective, equitable, and engaging educational experience for all.
Keywords: innovative technologies; pedagogical education; educational technology